Tradisi Karia pada Masyarakat di Desa Masalili Kecamatan Kontunaga Kabupaten Muna - Ela sri wahyuni; Wa Kuasa Baka; Shinta Arjunita Saputri (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
Research on Karia tradition aims to describe the process of implementing Karia tradition in Masalili Village, Kontunaga District, Muna Regency and analyze the meaning of materials and tools used in the process of implementing Karia tradition in Masalili Village, kontunaga District, Muna Regency. Research methods in data collection are conducted by observation techniques (observation), interviews and documentation. The informant technique uses purposive techniques. Data is analyzed by data collection techniques, data reduction, data presentation, and conclusion drawing (verification). Research methods in data collection are carried out by observation techniques (observation), interviews and documentation. The informant technique uses purposive techniques. Data is analyzed by data collection techniques, data reduction, data presentation, and conclusion drawing (verification). This research uses the theory of semiotics Charles Sanders Peirce posits that the theory of semiotics is based on logic, because logic studies how people reason besides it does signs that allow us to think relate to others and give meaning to what is displayed by the universe. The results of this study show that in the process of implementing the Karia tradition has 2 stages, namely (1) the preparation stage consisting of Karia participants and deliberation. (2) The implementation stages consisting of the recitation of the Bharasanji prayer (recitation of Sholawat), Kafoluku, Kaghombo, Kafosampu, Katandano Wite, Linda Dance, and finally Kaghorono Bhansa. The importance of materials and tools that contain meaning in the Karia procession, namely the collection of Kaghombo water, is interpreted as the purity of Karia participants, which means that all their ugliness has disappeared according to the pouring of Kaghombo water bathed by Pamantoto. Then the use of coconut mayang and areca nut (bhansa) is interpreted as that the Karia participants have grown up and. For the tools used in the accompaniment of the Karia procession, namely gongs and drums called rambi wuna which has a meaning as a sign of notification in the form of an invitation to the community to attend the Karia ceremony so that the atmosphere is always crowded.